Global Research Trends and Developments in Central Bank Digital Currencies (CBDCs) - Judijanto, Loso; Ar, Nursyam; Syamsinar, Syamsinar (The Es Economics and Entrepreneurship, 2025)
This study explores global research trends and developments in Central Bank Digital Currencies (CBDCs) using a bibliometric approach based on data retrieved exclusively from the Scopus database. With the rapid evolution of digital financial infrastructure and growing interest from policymakers and researchers alike, CBDCs have emerged as a critical area of academic inquiry. Utilizing VOSviewer, this study analyzes publication growth, leading contributors, co-authorship patterns, thematic clusters, and citation impact from 2010 to 2024. The results reveal a significant acceleration in research output, particularly from 2020 onwards, driven by practical initiatives from central banks and international financial institutions. Influential authors and institutions—including the Bank for International Settlements, International Monetary Fund, and several leading universities—play a central role in shaping the discourse. Thematic analysis highlights dominant research areas such as monetary policy, blockchain technology, financial stability, privacy, and financial inclusion, with emerging interest in regional implementations like the digital euro and eNaira. Co-authorship and country collaboration maps indicate a highly interconnected global research network, though disparities exist in regional participation. This study contributes to a deeper understanding of the intellectual structure of CBDC research and provides a foundation for future academic and policy-oriented work in the evolving landscape of digital currencies.